Family support in caring for family members with mental disorders and its impact on family life - Nurasiah Nurasiah; Raini Diah Susanti; Ahmad Yamin (Lentera Negeri, 2026)
This study examines the role of family support in caring for members with mental disorders and its impact on overall family life. The research addresses the challenges families face, including emotional fatigue, financial strain, and role conflicts, while highlighting the critical role of emotional, informational, and instrumental support in patient care and family cohesion. The study employs a literature-based methodology, analyzing primary and secondary data from books, journals, articles, and reports relevant to the phenomenon of family caregiving. Findings indicate that families provide multidimensional support that enhances patient recovery, treatment adherence, and family resilience, while coping strategies, social networks, and cultural context significantly influence caregiving effectiveness. The study concludes that family support is essential for both patient well-being and family stability, emphasizing the need for culturally sensitive, comprehensive, and collaborative approaches to strengthen caregiving practices and improve the quality of family life.